Dexamethasone Addition to Popliteal Nerve Blocks: Effects on Duration of Analgesia and Incidence of Postoperative Nerve Complication. Issue 1 (February 2021) - Noori, Naudereh; Anand, Kapil; Pfeffer, Glenn; Thordarson, David
Background . The purpose of this prospective, double-blinded randomized control pilot study was to evaluate the effect of adjunctive dexamethasone on analgesia duration and the incidence of postoperative neuropathic complication. Peripheral nerve blocks are an effective adjunct to decrease postoperative pain in foot and ankle surgery, and any possible modalities to augment their efficacy is of clinical utility. Methods . Patients were randomly assigned to a control group (n = 25) receiving nerve blocks of bupivacaine and epinephrine or an experimental group (n = 24) with an adjunctive 8 mg dexamethasone. The patients, surgeons, and anesthesiologists were all blinded to allocation. Patients had a minimum 1 year postoperative follow-up. Results . Forty-nine patients completed the protocol. There was no statistically significant difference in analgesia duration ( P = .38) or postoperative neuropathic complication incidence ( P = .67) between the 2 groups. Conclusions . The addition of dexamethasone to popliteal nerve blocks does not appear to affect analgesia duration or incidence of postoperative neuropathic complications. However, our study was underpowered, and we recommend a larger scale prospective study for validation. Levels of Evidence: Level II: Prospective, randomized control pilot study